2007
DOI: 10.1038/ncpneuro0372
|View full text |Cite
|
Sign up to set email alerts
|

Technology Insight: recanalization with drugs and devices during acute ischemic stroke

Abstract: Revascularization therapy is pivotal to saving ischemic brain from infarction. Two major randomized trials of intravenous thrombolytic therapy have established clear clinical benefit, especially for strokes caused by small-vessel occlusion. Ischemic stroke caused by large-vessel intracranial occlusion carries higher morbidity, however, and intravenous thrombolytics are less capable of opening these large vessels. This observation makes a case for delivering thrombolytics directly into the clot, or simply remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Recently, recanalization with drugs during acute ischemic stroke have been shown to be clinically effective for treating ischemic stroke [24]. Thus, a reliable animal model of transient focal ischemia is becoming more important in order to study the pathophysiology of ischemic stroke and evaluate new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, recanalization with drugs during acute ischemic stroke have been shown to be clinically effective for treating ischemic stroke [24]. Thus, a reliable animal model of transient focal ischemia is becoming more important in order to study the pathophysiology of ischemic stroke and evaluate new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The technical efficacy and safety profile of the Merci ® Retriever device have been evaluated in prospective trials of patients with large-vessel stroke treated within 8 h. 11,12 These trials showed recanalization rates that ranged from 46% to 69%, depending on whether adjunctive therapies were used, and also that good neurologic outcomes were more frequent, and mortality was lower, in patients with successful recanalization. 13 Several ongoing trials comparing mechanical and medical reperfusion therapies will also evaluate whether multimodal MRI can identify those patients likely to benefit from each treatment, as well as those likely to be harmed. 14 …”
Section: Treatment and Managementmentioning
confidence: 99%
“…Intravenous and intra-arterial thrombolysis combined with mechanical thombectomy is a promising option, especially in patients with high clot burden and proximal vessel occlusion, as suggested by Smith [5]. Venker et al [6] examined this approach with the Solitaire stent device in the anterior circulation in 10 patients.…”
Section: Interventional Treatment Strategymentioning
confidence: 99%
“…One fundamental prognostic factor is rapid recanalization by early percutaneous treatment [4]. Without treatment, the prognosis of VBO is almost always fatal, with mortality rates from 80% to 90% [5,6].…”
Section: Introductionmentioning
confidence: 99%